2013
DOI: 10.1259/bjr.20130385
|View full text |Cite
|
Sign up to set email alerts
|

Image guidance protocols: balancing imaging parameters against scan time

Abstract: Objective: Optimisation of imaging protocols is essential to maximise the use of image-guided radiotherapy. This article evaluates the time for daily online imaging with TomoTherapy® (Accuray®, Sunnyvale, CA), separating mechanical scan acquisition from radiographer-led image matching, to estimate the time required for a clinical research study (VoxTox). Methods: Over 5 years, 18 533 treatments were recorded for 3 tumour sites of interest (prostate, head and neck and central nervous system). Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We chose patients who were treated with radiotherapy to pelvic lymph nodes as well as the prostate, as our previous work had demonstrated that the image guidance scans for this group were longer in the SI direction than for patients having their prostate alone treated. 20 The rectum was analysed in thirds, which is the traditional anatomical approach for this organ. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…We chose patients who were treated with radiotherapy to pelvic lymph nodes as well as the prostate, as our previous work had demonstrated that the image guidance scans for this group were longer in the SI direction than for patients having their prostate alone treated. 20 The rectum was analysed in thirds, which is the traditional anatomical approach for this organ. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Researchers argued that normal MVCT scans are superior to coarse scan for the registration of shifts in the superior–inferior directions, with an improvement in residual error of about 0·4 mm evaluated from a head phantom 15 . The spatial resolution in the longitudinal direction may be slightly compromised, but the axial resolution of coarse scan does not degrade significantly 16 …”
Section: Discussionmentioning
confidence: 99%
“…15 The spatial resolution in the longitudinal direction may be slightly compromised, but the axial resolution of coarse scan does not degrade significantly. 16 To date, Ho et al and Woodford et al agreed that images acquired in coarse scans under its corresponding reconstruction slice thickness showed no significant image quality degradation and low residual error in contrast to normal and fine mode in 4 slices/gantry rotation reconstruction. 17,18 These non-significant differences have pronounced the possibility of selecting the coarse mode for MVCT verification in routine practice so as to keep the radiation dose as minimal as possible.…”
Section: Optimisation On Imaging Modementioning
confidence: 93%
“…MVCT specifications were: 512 × 512 pixels per slice, pixel size 0.754 mm, slice thickness 6 mm. The field of view for MVCT imaging was limited to typically 8–12 slices according to local protocols to minimise additional dose and time for prostate IGRT (Bates et al 2013), so only a proportion of the rectum was imaged.…”
Section: Methodsmentioning
confidence: 99%